Welcome to our community

Be a part of something great, join today!

Rearranging formula 3y + x = -1

gazparkin

New member
Jul 1, 2019
17
Hello,

I'm trying to work out the individual steps to get from


start: 3y + x = -1

to: 3y = -x -1

to: y = - 1/3x -1/3

Could anyone help me with this!

Thank you :)
 

skeeter

Well-known member
MHB Math Helper
Mar 1, 2012
613
North Texas
$3y+x=-1$

subtract $x$ from both sides ...

$3y = -x-1$

divide all terms by 3 ...

$\dfrac{3y}{3} = -\dfrac{x}{3} - \dfrac{1}{3}$

$\dfrac{\cancel{3}y}{\cancel{3}} = -\dfrac{x}{3} - \dfrac{1}{3}$

$y = -\left(\dfrac{x}{3} + \dfrac{1}{3}\right)$

$y = - \dfrac{x+1}{3}$